Pengaruh Profitabilitas, Ukuran Perusahaan, Tanggung Jawab Sosial dan Struktur Modal Terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI Periode 2018-2021 - Lili Suryani Umar; M. Cholid Mawardi; Hariri Hariri (Universitas Islam Malang, 2023)
The purpose of this study is to determine the effect of profitability, company size, social responsibility, and capital structure on company value in manufacturing companies in the consumer goods industry sector listed on the IDX for the 2018-2021 period. The population of this study is manufacturing companies in the consumer goods industry sector listed on the IDX for the 2018-2021 period. The samples used were 19 samples of companies that met the criteria in the research subject with 4 years of research years, namely 76 total samples. The analysis methods used are multiple regression equations, normlity tests, classical assumption tests, descriptive statistical analysis and hypothesis tests. The results showed that Profitability and Capital Structure partially affect the Company Value in manufacturing companies in the consumer goods industry sector listed on the IDX for the 2018-2021 period. Meanwhile, company size and social responsibility partially have no effect on the Company Value of manufacturing companies in the consumer goods industry sector listed on the IDX for the 2018-2021 period.Keywords: Profitability, company size, social responsibility, capital structure and company value.